Exploring Extended Configuration of Digital Eco-Dynamic Influence on Small E-Business' Product Innovation - Yuniarty, -; Gautama So, Idris; Bramantoro Abdinagoro, Sri; Hamsal, Mohammad (JOIV : International Journal on Informatics Visualization, 2022)
This study comprehensively explores the factors affecting product innovation performance in small e-businesses. The effects of the broader composition of digital eco-dynamics on the performance of product innovation of small businesses are little understood. This study tries to fill in the gaps and investigate the interdependencies above. This study offers the novelty of using RICH as a construct that can improve innovation performance, expanding on a digital eco-dynamic that has not been developed for ten years. Confirmatory factor analysis, descriptive statistics, construct reliability, average variance extracted, and the RMSEA model of fit test was used to analyze data from 300 useable responses. The test reliability and validity of the empirical model were evaluated through linguist reviews and statistically tested with construct reliability coefficients and confirmatory factor analysis. The findings also suggest that IT capability, dynamic capability, environmental uncertainty, and resource induce coping heuristics positively impact product innovation performance in small e-businesses. This research will contribute to developing innovation theory by offering RICH as a solution. The finding that RICH is positively and significantly related to innovation performance is significant for business actors, mainly because it is in the context of developing countries. For entrepreneurs, the findings of this study suggest that developing resources in a manner consistent with the RICH strategy for companies to be more entrepreneurially oriented. In this way, the development and actualization of cognitive resources can reduce uncertainty and lead to resource acquisition and resource protection by entrepreneurs